Hjärtfrekvensvariabilitet hos friska hundar - Törner, Maria (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2010)
In healthy dogs, heart rate fluctuates during the day. Heart rate variability (HRV) reflects the autonomic nervous system´s regulation of the cardiovascular unit. Heart rate variability shows the balance between the sympathetic and parasympathetic nervous system, also called sympathovagal balance. Heart rate variability can be measured by time domain - and frequency domain analysis. In a time domain analysis you study the beat-to-beat-interval (RR-interval) in an electrocardiogram (ECG), while a frequency domain analysis can be used to determine the size of the variability. The high frequency bands (HF) in a frequency spectrum represent the parasympathetic activity, the low frequency bands (LF) reflect both the sympathetic and parasympathetic activity and the ratio LF:HF represents the sympathovagal balance. Many factors can influence HRV in healthy dogs. The purpose of this study is to elucidate some of these factors and further on how they affect the HRV. One of these factors that influence HRV is type of breed. By vaso-vagal tonus index (VVTI), which registers HF, you can see divergences between different kinds of breeds. The brachycephalic breeds have higher VVTI than non-brachycephalic. Further on a connection between size of HRV and age can be found. The heart rate variability is lower in older individuals. HRV is also influenced by circadian rhythms, body position and to some extent also gender. Finally, low HRV is associated with stress and some diseases, which is important within diagnostics and preoperative care.